New Design of Channel Drop Filter by Triangular Photonic Crystal - Mohammad Reza Rakhshani; MohammadAli Mansouri Birjandi (International Journal of Electrical and Computer Engineering (IJECE), 2013)
We have designed a new type of optical channel drop filter (CDF) based on two dimensional triangular lattice photonic crystals. CDF operation is based on coupling to the photonic crystal waveguide. The proposed structure is optimized to work as a CDF. For obtaining the CDF characteristics and band structure of the filter, the finite difference time domain (FDTD) method and plane wave expansion (PWE) method are used respectively. Dropping efficiency at 1556nm and quality factor (Q) of our proposed structure are 100% and 260, respectively. The quantities of quality factor and transmission efficiency are suitable for optical applications. The overall size of the proposed add drop filter is 191.97µm2, which is smaller than the filters already reported and it is highly desirable for photonic integrated circuits (PICs).DOI:http://dx.doi.org/10.11591/ijece.v3i1.1931